Targeted simplification versus antipseudomonal broad-spectrum beta-lactams in patients with bloodstream infections due to Enterobacteriaceae (SIMPLIFY): a study protocol for a multicentre, open-label, phase III randomised, controlled, non-inferiority clinical trial. Issue 6 (9th June 2017) - López-Cortés, Luis Eduardo; Rosso-Fernández, Clara; Núñez-Núñez, María; Lavín-Alconero, Lucía; Bravo-Ferrer, José; Barriga, Ángel; Delgado, Mercedes; Lupión, Carmen; Retamar, Pilar; Rodríguez-Baño, Jesús
Abstract : Introduction: Within the context of antimicrobial stewardship programmes, de-escalation of antimicrobial therapy is one of the proposed strategies for reducing the unnecessary use of broad-spectrum antibiotics (BSA). The empirical treatment of nosocomial and some healthcare-associated bloodstream infections (BSI) frequently includes a beta-lactam with antipseudomonal activity as monotherapy or in combination with other drugs, so there is a great opportunity to optimise the empirical therapy based on microbiological data. De-escalation is assumed as standard of care for experts in infectious diseases. However, it is less frequent than it would desirable. Methods and analysis: The SIMPLIFY trial is a multicentre, open-label, non-inferiority phase III randomised controlled clinical trial, designed as a pragmatic 'real-practice' trial. The aim of this trial is to demonstrate the non-inferiority of de-escalation from an empirical beta-lactam with antipseudomonal activity to a targeted narrow-spectrum antimicrobial in patients with BSI due to Enterobacteriaceae . The primary outcome is clinical cure, which will be assessed at the test of cure visit. It will be conducted at 19 Spanish public and university hospitals. Ethics and dissemination: Each participating centre has obtained the approval of the ethics review committee, the agreement of the directors of the institutions and authorisation from the Spanish Regulatory Agency (Agencia Española del Medicamento y Productos Sanitarios). Data will be presented at international conferences and published in peer-reviewed journals. Discussion: Strategies to reduce the use of BSA should be a priority. Most of the studies that support de-escalation are observational, retrospective and heterogeneous. A recent Cochrane review stated that well-designed clinical trials should be conducted to assess the safety and efficacy of de-escalation. Trial registration number: The European Union Clinical Trials Register: EudraCT number 2015-004219-19. Clinical trials.gov: NCT02795949 . Protocol version: V.2.0, dated 16 May 2016. All items from the WHO Trial Registration Data Set are included in the registry.